Cellulose acetate and adsorbents supported on cellulose fiber extracted from waxy corn husks for improving shelf life of frying oil - Udomkun, Patchimaporn; Innawong, B.; Jumrusjumroendee, N. (Elsevier, 2018)
The efficacy of cellulose paper consolidated with cellulose acetate and mixed adsorbents (bentonite: activated clay: celite = 37.5: 50: 12.5 g with 1 g citric acid/100 g mixed adsorbents) on the physico-chemical properties of oil was evaluated during deep-fat frying of chicken nuggets for 7 days. Cellulose fiber and cellulose acetate were produced from waxy corn husks. Using adsorbents supported on cellulose fiber with or without cellulose acetate resulted in lower poly-unsaturated fatty acids (PUFAs), trans-fatty acid, free fatty acid (FFA), peroxide value (PV), and total polar materials (TPMs) compared with results from commercial filter paper (control). The L*, a*, and b* changes of treated oils were better than in control. Limiting the polarity in cellulose acetate might influence TPMs reduction but was more effective in overall quality improvement. The PUFAs, total trans-fatty acid, FFA, PV, and TPMs decreased by 1.8, 7.4, 37.0, 133.3, and 20.5%, respectively when compared with control. Therefore, the use of cellulose paper and cellulose acetate obtained from corn husks was found to significantly lengthen the life cycle of frying oil.